FACTORS THAT PROVIDE MOVEMENT OF LYMPHATICS OF RATS ON LYMPHATIC VASCULARS - . Myrzakhanova, M.N.; Myrzakhanov, N. (Academic Journal of Physical and Chemical Sciences, 2018)
Movement of lymph in the reduction of the vascular wall due to the existence of valves in the lymph vessels occurs only in one direction. Authors use the rat for experimental work. For a reliable interpretation of the data obtained from animal experiments on the human body, it is necessary to know the specific features of their structure. In the body, the movement of lymph along the vessels is facilitated by a number of secondary factors, so passing through the thoracic cavity, the duct accumulates lymph from the organs located there. Under the aorta, the caudal thoracic duct passes in the form of a broad cistern of the thoracic duct, moreover, the intestinal lymphatic duct starts. However, the thoracic duct is very thin and gently structured by semi-transparent or almost invisible without special devices of rat lines.